Optimization on the container loading sequence based on hybrid dynamic programming - Bian, Zhan; Shao, Qianqian; Jin, Zhihong (Transport, 2016)
Retrieving export containers from a container yard is an important part of the ship loading process during which arranging the retrieving sequence to enhance port efficiency has become a vital issue. This paper presents a twophase hybrid dynamic algorithm aiming at obtaining an optimized container loading sequence for a crane to retrieve all the containers from the yard to the ship. The optimization goal is to minimize the number of relocation operations which has a direct impact upon container loading operation efficiency. The two phases of the proposed dynamic algorithms are designed as follows: at the first phase, a heuristic algorithm is developed to retrieve the containers subset which needs no relocation and may be loaded directly onto the ship; at the second phase, a dynamic programming with heuristic rules is applied to solve the loading sequence problem for the rest of the containers. Numerical experiments showed the effectiveness and practicability of the model and the algorithm by comparing with the loading proposals from an existing research and actual rules respectively.First published online: 14 Jan 2015